Penggunaan Media Kartu Bergambar Untuk Meningkatkan Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun di Paud Kairatu Indah - Mercy F Halamury; Adelce Ririne; Wahyuni; Sandri Kabina; Nurlela Maempo; Elsera Ilelapotoa; Wasutiayani; Dessy Cornelia Kermite (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2026)
Abstract : This study aims to examine the use of picture cards as a medium to improve early reading skills among children aged 5–6 years at PAUD Kairatu Indah, Kairatu District, West Seram Regency. The research employed a qualitative approach with Classroom Action Research (CAR) conducted in two cycles. The subjects consisted of 13 children, including 5 boys and 8 girls. Data collection techniques included observation and documentation, analyzed using qualitative descriptive methods. The results indicate that the use of picture card media significantly enhances children’s early reading ability. In the pre-cycle, the average score of early reading skills was 34%, with 9 children categorized as Not Yet Developed (NYD) and 4 children Beginning to Develop (BD). In Cycle I, the score increased to 59.61%, with 6 children Developing as Expected (DAE), 6 children BD, and 1 child NYD. In Cycle II, the score rose to 88.46%, with 8 children categorized as Very Well Developed (VWD), 4 children DAE, and 1 child BD. In conclusion, picture card media is effective in improving early reading skills of children aged 5–6 years through visual, interactive, and enjoyable learning.   Keywords: Picture Cards; Early Reading; Early Childhood